Digitalisasi Cagar Budaya di Indonesia: Sudut Pandang Baru Pelestarian Cagar Budaya Masa Hindu-Buddha di Kabupaten Semarang - Aditya Revianur (Faculty of Cultural Sciences, 2020)
AbstractOur recent technologies, such as digital photography, 3D scanner, and augmented reality, provide an alternative idea to preserve cultural heritages, i.e. building, artefact, and structure. The main point of this article is to continue the discourse on the advantages of digital preservation on several cultural heritage sites in Semarang, called Ancient Medang Project. Semarang Regency located in Central Java Province that has many cultural heritages from ancient Java period, such as temples, artefact, sculptures, etc. However, mostly cultural heritages in Semarang Regency have been lost due to rapid modernization. The writer and several local communities who concern about cultural heritage preservation created a project to digitalize the cultural heritage in Semarang to prevent further destruction and encourage the importance of the cultural heritage sites to the public through digital media. This project is a multidisciplinary project that involved archaeologists, IT experts, and the local community to create an interactive system database regarding cultural heritages in Semarang. Three main perspectives were carried out to develop the project, i.e. content information based on archaeological surveys, construction of website design, and evaluation. The first perspective was used to collect information regarding the archaeological aspects of cultural heritage in Semarang. The second perspective was conducted to develop website prototype based on data from previous study. The final perspective was to evaluate and enhance the website prototype. The results show that the cultural heritage digitization is not only useful for preservation, but also for public engagement and facilitate cultural learning.———-AbstrakKemajuan teknologi terkini, seperti fotografi digital, pemindai 3D, dan augmented reality, memberikan ide alternatif untuk melestarikan warisan budaya, misalnya bangunan, artefak, dan struktur. Poin utama dari artikel ini adalah untuk melanjutkan wacana tentang manfaat digitalisasi pelestarian pada beberapa situs warisan budaya di Semarang, yang disebut dengan Proyek Medang Kuno. Kabupaten Semarang terletak di Provinsi Jawa Tengah yang memiliki banyak warisan budaya dari zaman Jawa kuno, seperti kuil, artefak, patung, tetapi sebagian besar warisan budaya di Kabupaten Semarang telah hilang karena modernisasi yang cepat. Penulis dan beberapa komunitas lokal yang peduli dengan pelestarian cagar budaya menciptakan sebuah proyek untuk mendigitalkan cagar budaya di Semarang untuk mencegah perusakan lebih lanjut dan mendorong pentingnya situs cagar budaya kepada publik melalui media digital. Proyek ini adalah proyek multidisiplin yang melibatkan arkeolog, pakar IT, dan masyarakat setempat untuk membuat basis data sistem interaktif mengenai warisan budaya di Semarang. Tiga perspektif utama dilakukan untuk mengembangkan proyek, yaitu informasi konten berdasarkan survei arkeologi, konstruksi desain situs web, dan evaluasi. Perspektif pertama digunakan untuk mengumpulkan informasi mengenai aspek arkeologis warisan budaya di Semarang. Perspektif kedua dilakukan untuk mengembangkan prototipe situs web berdasarkan data dari penelitian sebelumnya. Perspektif ketiga adalah untuk mengevaluasi dan meningkatkan prototipe situs web. Hasilnya menunjukkan bahwa digitalisasi warisan budaya tidak hanya berguna untuk pelestarian, tetapi juga untuk keterlibatan publik dan memfasilitasi pembelajaran budaya.